Developing a professional teaching portfolio: a guide for success - Constantino, Patricia M.; De Lorenzo, Marie N. (Boston, 2006)
The edition provides a step by step practical resource for successsfully developing a professional teaching portfolio, both paper and electronic.
Keywords: Portfolios in Education; Teachers-Rating Of-United States; Teachers-Training Of- United States